The Impact of Sr Content on Fe - Intermetallic Phase's Morphology Changes in Alloy AlSi10MgMn - Borko, Kamil; Tillova, Eva; Chalupova, Maria (Manufacturing Technology Journal, 2016)
The effect of modification (with AlSr10) on the microstructure of hypoeutectic AlSi10MgMn cast was systematically investigated. The samples were studied in as cast state without Sr (0 % Sr) and after modification (0.05 % Sr; 0.1 % Sr and 0.15 % Sr). Iron is added to Al-Si alloy to increase hot tear resistance and to reduce die sticking, but can change the solidification characteristics by forming pre- and post-eutectic β-Al5FeSi phase or other Fe-rich phases, which can be very detrimental to the mechanical properties of the final cast part. A combination of different analytical techniques (light microscopy upon black-white etching; scanning electron microscopy (SEM) upon deep etching and energy dispersive X-ray analysis (EDX); quantitative phase analyse upon Image analyzer NIS Elements 3.0) were therefore been used for the microstructure study. The results show that the addition of Sr into AlSi10MgMn cast alloy modified eutectic silicon as well as Fe-intermetallic phases and improves mechanical properties (ductility, strength).
Keywords: aluminium cast alloy; microstructure; Fe-rich phases and morphology